Influence of Vitamin D Supplementation on Serum Hepcidin Levels among Non-Diabetic Chronic Kidney Disease Patients: A Randomized Study - Himadri Shankar (Student’s Journal of Health Research Africa, 2024)
Background Vitamin D, a fat-soluble vitamin, is necessary for many body processes, such as controlling the metabolism of calcium and phosphorus and preserving strong bones. The objective of the study was to find out how cholecalciferol supplementation affected the levels of hemoglobin, 25(OH)D, and hepcidin in serum in non-diabetic individuals with stage III-IV CKD and vitamin D deficiency. Methods A randomized, double-blind, placebo-controlled experiment included 140 non-diabetic stage III–IV CKD patients aged 18–70 with vitamin D insufficiency. The cholecalciferol group (n = 70) received two oral doses of 300,000 IU at baseline and eight weeks, while the placebo group (n = 70) received identical placebo dosages. Follow-ups were done at 16 weeks. IBM SPSS Statistics 21.0 was used to measure and analyze serum 25(OH)D, hepcidin, hemoglobin, and other biochemical data. Results There were 140 people, 70 per group. Age differences between categories were not significant (p = 0.742). The gender distribution was identical with 52% of males in category I and 50% in category II (p = 0.819). After 16 weeks, the cholecalciferol group had significantly higher serum 25(OH)D levels (11.3 ng/ml) compared to the placebo group (1.5 ng/ml; p < 0.001). Serum hepcidin levels declined significantly (-3.2 ng/ml) in the cholecalciferol group compared to the placebo group (-0.5 ng/ml; p = 0.002). Category I serum hemoglobin levels showed a significant increase (1.2 g/dL) over category II (0.3 g/dL; p = 0.008). Conclusion In non-diabetic CKD patients, cholecalciferol administration resulted in considerably higher serum 25(OH)D levels and lower serum hepcidin levels. It also raised hemoglobin levels, suggesting that it might help treat anemia linked to chronic kidney disease. Recommendations To effectively manage anemia and other problems in individuals with CKD, more extensive studies are required to confirm these findings and optimize vitamin D administration strategies.